HERD MENTALITY DALAM ISLAM DIGITAL: KEARIFAN NABI DI ERA MEDIA SOSIAL DAN TREN VIRAL - Akib, Moh.; Hafizi, Saidul; Jauhari Asyhar, Achmad (MAHABBAH : Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2025)
The phenomenon of herd mentality has intensified in the digital era, particularly in religious interactions on social media. This article explores how the Prophet’s hadiths provide insights into addressing this phenomenon by emphasizing critical thinking and media literacy. The study aims to analyze the impact of herd mentality in digital Islam and examine how the Prophet's teachings promote a balance between following the majority and independent reasoning. This research employs a qualitative method with a content analysis approach, examining hadiths related to social conformity, critical thinking, and information dissemination. Additionally, it investigates the virality phenomenon in Islamic discourse on social media through case studies. he findings indicate that herd mentality in the digital realm can lead to the spread of unverified religious information, reinforce religious polarization, and create echo chambers that hinder critical thinking. The Prophet’s hadiths emphasize the importance of tabayyun (verification of information), caution against hastily accepting information, and maintaining a balance between following the community and critically assessing the majority's influence. In conclusion, the Prophet’s teachings offer relevant principles to counter the negative effects of herd mentality in the age of social media. By applying values such as tabayyun and critical thinking, Muslims can navigate viral religious trends more wisely and avoid falling into untested collective thought patterns.